Genetic Analysis of Functions Involved in Adhesion of Pseudomonas putida to Seeds - Espinosa-Urgel, Manuel (American Society for Microbiology, 2000)
Many agricultural uses of bacteria require the establishment of efficient bacterial populations in the rhizosphere, for which colonization of plant seeds often constitutes a critical first step. Pseudomonas putida KT2440 is a strain that colonizes the rhizosphere of a number of agronomically important plants at high population densities. To identify the functions involved in initial seed colonization by P. putida KT2440, we subjected this strain to transposon mutagenesis and screened for mutants defective in attachment to corn seeds. Eight different mutants were isolated and characterized. While all of them showed reduced attachment to seeds, only two had strong defects in their adhesion to abiotic surfaces (glass and different plastics). Sequences of the loci affected in all eight mutants were obtained. None of the isolated genes had previously been described in P. putida, although four of them showed clear similarities with genes of known functions in other organisms. They corresponded to putative surface and membrane proteins, including a calcium-binding protein, a hemolysin, a peptide transporter, and a potential multidrug efflux pump. One other showed limited similarities with surface proteins, while the remaining three presented no obvious similarities with known genes, indicating that this study has disclosed novel functions.